Parameters of situational motor skills of Serbian swimmers and their influence on swimming results - Jorgic, B.; Okicic, T.; Stankovic, R.; Dopsaj, M.; Madic, D.; Thanopoulos, V. (Facta Universitatis: Series Physical Education and Sport, 2011)
In addition to basic motor skills in swimming, it is important to monitor and develop situational motor skills. Situational motor skills can be determined during immediate competitive activities since these activities are conducted in an objective reality, i.e. the reality of a competition for an athlete. The parameters of situational motor skills can be used in two ways - for a comparison of swimmers with each other and for determining the effects of certain parameters on swimming results. The aim of this paper is to determine the parameters of situational motor skills and their influence on the outcome in the 50m freestyle in the Serbian Open. The sample of participants comprised of 14 Serbian swimmers who participated in the A and B finals in the 50m freestyle swim race at the Open Championship of Serbia (Serbia Open 2010). Among the swimmers who were examined, there were nine members of the Serbian national team. The sample of variables consisted of four predictor variables and one criterion variable. To estimate the parameters of situational motor skills (predictor variables), the following tests were used: stroke length (SL), stroke rate (SR), stroke index (SI) and stroke efficiency (SE). The criterion variable was the result of the 50m freestyle swim (R50F). The results obtained in this study indicate that in this group of elite Serbian swimmers, the greatest impact of the outcome in the 50 meter freestyle swim can be ascribed to stroke length (SL) and the stroke index (SI). When freestyle sprinters are being examined, it is necessary to define the situation model of the given parameters regarding their gender, age and the competitive level of the swimmers. It is also necessary to monitor the change of these indicators in the function of the individual training season, and many years of training. Accordingly, it is necessary to conduct the relevant training process.